Influence of the antifolate drug Methotrexate on the development of murine neural tube defects and genomic instability. Issue 9 (13th July 2012) - Zhao, Jie; Guan, Tao; Wang, Jianhua; Xiang, Qian; Wang, Mingsheng; Wang, Xiuwei; Guan, Zhen; Xie, Qiu; Niu, Bo; Zhang, Ting
ABSTRACT: Impaired folate metabolism is considered a risk factor for neural tube defects (NTDs). However, the relationship between folate deficiency and the risk of NTDs remains unclear, because experimentally induced dietary folate deficiency is insufficient to cause NTDs in non‐mutant mice. Methotrexate (MTX) is a specific folate antagonist that competitively inhibits dihydrofolate reductase (DHFR) activity. The objective of this study was to develop a folate dysmetabolism murine model, and study the development of NTDs and its mechanism. Pregnant mice were injected with different doses of MTX [0, 0.5, 1.0, 3.0, 4.5 and 6.0 mg kg –1 body weight (b/w) intraperitoneally (i.p.)] on gestational day 7.5 and sacrificed on gestational day 11.5. DHFR activity in embryonic tissues was detected, and folate concentrations were analyzed using LC/MS/MS. Copy number variations (CNVs) in neural tube tissues were detected using array comparative genomic hybridization (aCGH). A dose of MTX 4.5 mg kg –1 b/w, resulted in the highest incidence of NTDs (31.4%) compared with the other groups, and DHFR activities, 5‐MeTHF and 5‐FoTHF concentrations in embryonic tissues decreased significantly after MTX injection. Furthermore, we found three high‐confidence CNVs on chromosome X using aCGH, which was confirmed by RT‐PCR and MassARRAY. These results indicate that MTX could cause a folate‐associated dysmetabolism, which is similar to that of dietary folate deficiency in mice. The presence of CNVs in neural tube tissues was associated with the development of NTDs. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Impaired folate metabolism is considered a risk factor for neural tube defects (NTDs), but the relationship between folate dysmetabolism and NTDs remains unclear. The objective of this study was to develop a NTD model, and study the mechanism of NTDs. Methotrexate (MTX), a folate antagonist, induced NTDs in mice, and dihydrofolate reductase (DHFR) activity and folates derivatives concentrations of embryonic tissues decreased significantly. Furthermore, three high‐confidence copy number variants (CNVs) were found on chromosome X, which in neural tube tissues may contribute to the development of NTDs.